Impact of Social Forestry Licensing Policy: Community Plantation Forest for Charcoal Production in the Mangrove Ecosystem of Karimun Regency, Kepulauan Riau Province - Andia, Bherly; Ismail, Khodijah; Sofia, Myrna; Haryanti, Dewi; Habibah, Sayyidah Nur (Jurnal Perikanan dan Kelautan, 2024)
This research analyses the suitability of permits for using mangrove wood in Karimun Regency for charcoal making, which has been going on for a long time. This charcoal was traded for local and foreign needs even before Indonesian Independence. However, it was only in 2010 that the official IUPHHK-HTR permit was enacted to regulate this activity. This study aims to analyze the suitability of forest area functions in community plantation forest permit areas based on the provisions of forestry laws and regulations, calculate the area of degraded/deforested as well as reforested forest cover using satellite image interpretation results, and identify institutions involved in processing mangrove wood into charcoal. The results showed that 59.55% of the forest area followed the permit, but there was deforestation of 802.29 ha (27%) and degradation of 72.53 ha (32.44%). On the other hand, reforestation efforts of 1,446.32 hectares were also carried out. This research was conducted using normative or doctrinal legal and overlay methods. The methods used in this research consist of normative or doctrinal legal research methods and overlay methods. Normative legal research focuses on the scope of legal conceptions, legal principles, and legal rules governing the suitability of forest area functions and granting social forestry licenses for community plantation forests. At the same time, the overlay method combines information from various maps. Various parties are involved in mangrove charcoal management, ranging from the Ministry of Environment and Forestry, Kepulauan Riau Provincial Government, Karimun Regency Government, and Wana Jaya Karimun Cooperative to 30 business license holders and charcoal collectors. This research recommends evaluating mangrove IUPHHK-HTR policies to ensure forest sustainability and balance between utilization and sustainability.